#TITLE_ALTERNATIVE# - RACHMANIAR (NIM : 10107053); Dosen pembimbing : Dr. Djoko Suprijanto, RANNY
Binary linear code can be defined by constructing generator matrix from adjacency matrix of undirected graphs. A binary linier code which is constructed by a high dimensional adjacency matrix of undirected graf will always accomplish Gilbert-Varshamov bound. It is well-known that from strongly regular graphs we can obtain nearly optimal and optimal codes. Moreover, strongly regular graphs can be operated to get a new graph and, as a by-product, a new code. In this final project, we observe four kind of operations on graph theory: union, join, product, and line graph. By using line graph operation, we get several codes which are nearly optimal and optimal.